Circular economy in construction: A systematic review of knowledge gaps towards a novel research framework - Gasparri, Eugenia; Arasteh, Samaneh; Kuru, Aysu; Stracchi, Paolo; Brambilla, Arianna (Frontiers in Built Environment, 2023)
The current growing interest in the circular economy offers extensive opportunities to promote the adoption of more sustainable consumption and production practices across industries, which is a top priority in achieving the United Nations' Sustainable Development Goals. The construction sector's shift towards circular models is key to reducing carbon emissions and resource depletion but brings along considerable complexities and challenges, given the industry`s fragmented and conservative nature. Research on the circular economy in construction has been growing exponentially over the past few years, producing a substantial amount of new knowledge in a short time. This study conducted a systematic review to map and synthesise the reported knowledge gaps in the literature.The analysis included forty-one (41) articles published between 2017 to 2022. One hundred fifty-five (155) knowledge gaps were identified and categorised according to seven (7) CE research dimensions -economic, environmental, governmental, methodological, societal, sectoral, and technological -and twenty-six (26) thematic sub-clusters. Findings critically analyse knowledge gaps' frequency of occurrence over time and across dimensions. A new framework for CE implementation is proposed to support critical discussion and identification of future research trajectories towards a systemic transition to a circular economy in the construction sector. The framework identifies three innovation domains: circular product, circular process, and circular platform.